WANITA USIA 26 TAHUN, MULTIGRAVIDA HAMIL 35 MINGGU DENGAN DIAGNOSIS INFEKSI SALURAN KEMIH - Muhammad Luthfi Adnan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2019)
Urinary tract infection (UTI) is a disease caused by bacteria that attack theurinary tract. Pregnant women are one of the risk factors for the occurrenceof UTI and are at risk of causing premature birth and low birth weight (LBW).This case report describes multigravida women with G3P1A1Ah1 with agestational age of 35 weeks less 2 days with complaints of tightness,frequent urination at night and lower back pain. The patient has a history ofcesarean section at the birth of the first child and the incidence of UTI beforemarriage. Blood pressure: 102/71 mmHg with pulse 90 times / minute. FH29 cm with EFW ± 2790 grams, right back, head presentation, had enteredthe pelvis with a 4/5 decline, His palpitations were not palpable, fetal heartrate was 135x / minute and irregular rhythm. On laboratory examinationshows the results of hemoglobin (Hb) examination of 12.8 g / dL and leukocytes exceed the normal threshold (5000-15000 / mm3). The patient isthen given calcium lactate, iron fumarate to maintain pregnancy andamoxicillin to treat UTI in patients. Patients are also educated to maintainthe cleanliness of genital organs to prevent further infection and advise ifwant to start family plan program, patient can use Intrauterine Device (IUD)as contraception.